Low-wage employment versus unemployment: which one provides better prospects for women? - Alexander Mosthaf; Thorsten Schank; Claus Schnabel (Institute for the Study of Labor (IZA), 2009)
This study analyzes state dependence in low-wage employment of western German women using GSOEP data, 2000-2006. We estimate dynamic multinomial logit models with random effects and find that having a low-wage job increases the probability of being low-paid and decreases the chances of being high-paid in the future, in particular for low-paid women working part-time. However, concerning future wage prospects low-paid women are clearly better off than unemployed or inactive women. We argue that for women low-wage jobs can serve as stepping stones out of unemployment and are to be preferred to staying unemployed and waiting for a better job.
Keywords: J30; J60; C33; 330; Low-pay dynamics; state dependence; dynamic multinomial logit model; Frauenerwerbstätigkeit; Niedriglohn; Frauenarbeitslosigkeit; Berufliche Integration; Deutschland